Water Infiltration into Uniform and Stratified Soils - ASSEED, MOHAMED; SWARTZEN DRUBER, D. (The Libyan Journal of Agriculture, 2023)
The equations of the approximate infiltration theory of Green and Ampt are much simpler than the mathematical forms of the diffusivity-conductivity theory ofsoil-water movement, and also involve parameters of characterization that are easier to measure experimentally. For cumulative water infiltrated into uniform soil as a function of time, these parameters are: the initial water content of the soil, the constant mean water content behind the wet front, a soil constant akin to the hydraulic conductivity of nearly saturated soil, and an equivalent constant head of water arising from the capillary properties of the soil. For fitting of the Green and Ampt equation to experimental infiltration data, a least-squares approach was developed, and was found to work very satisfactorily for measurements made on sand-silt mixtures. The approximate theory was applied to infiltration into stratified soils, thus involving the parameters of characterization of each stratum. Analysis was carried out for two and three strata, and can be continued for as many strata as desired. The resulting equations, however, become increasingly complicated, especially for the larger values of time at which the wet front has advanced into successively deeper strata.